Vibrational Quenching of Weakly Bound Cold Molecular Ions Immersed in Their Parent Gas - Krzysztof Jachymski; Florian Meinert (Applied Sciences, 2020)
Hybrid ion–atom systems provide an excellent platform for studies of state-resolved quantum chemistry at low temperatures, where quantum effects may be prevalent. Here we study theoretically the process of vibrational relaxation of an initially weakly bound molecular ion due to collisions with the background gas atoms. We show that this inelastic process is governed by the universal long-range part of the interaction potential, which allows for using simplified model potentials applicable to multiple atomic species. The product distribution after the collision can be estimated by making use of the distorted wave Born approximation. We find that the inelastic collisions lead predominantly to small changes in the binding energy of the molecular ion.